Formulation and Evaluation of Darunavir Ethanolate Nanogel as Microbicide in Pre-Exposure Prophylaxis for HIV Infection - Bandivadekar, Mithun; Madgulkar, Ashwini; Rashid, Syed Mubashir; Padakanti, Ranjitkumar; Godbole, Vedanti (International Journal of Pharmaceutical Investigation, 2025)
Background Anti-retroviral drugs are challenging formulation scientists due to their poor solubility problem. This criticality increases when the drug has to be delivered by a vaginal route where the availability of fluid to solubilize the drug is less. Purpose The Darunavir Ethanolate nano gel was prepared to aim to increase its solubility and improve the dissolution profile to be delivered in the vaginal route for prophylaxis treatment of HIV. Materials and Methods Phase solubility study of Darunavir Ethanolate: Hydroxypropyl-β-cyclodextrin was performed (simulated vaginal fluid). Inclusion complex formation was confirmed by FTIR studies. Nanogel was synthesized using the emulsion solvent evaporation method and evaluated for particle size, polydispersity index, zeta potential and entrapment efficiency. Solubility enhancement study of optimized batch in simulated vaginal fluid at different pH conditions was compared with pure drug. Results The phase solubility diagram showed the AL type of curve indicating 1:1 complex formation with a stability constant of 618.071 M-1. The formulated nanogel batch F8 with particle size 338.8 nm, PDI; 0.344, zeta potential; -40.3 mV and % entrapment efficiency; 93.52 was selected as the optimized batch. Nanogel showed a 40.9753, 56.9891 and 100.91-fold increase in drug solubility compared to the pure drug in simulated vaginal fluid at pH 3.5, 4.5 and 5.5 respectively. (%) Cumulative drug release of 83% at 22 hr, drug flux at 0.4421 µg/cm2/hr was observed. The best-fit model was the Korsmeyer-Peppas model followed by the Higuchi and the Zero-order models. Conclusion The formulated nano gel showed increasing solubility and dissolution profile of Darunavir Ethanolate to be administered in the vaginal cavity for prophylaxis treatment of HIV.
Keywords: Darunavir Ethanolate; Nanogel; Emulsion-solvent evaporation method; HIV; Microbicide